Navigating political risk in multinational business operations : An emerging market perspective - Raitanen, Olivia (My University, 2024)
The purpose of this bachelor’s thesis is to examine how political risks affect the internationalization of multinational enterprises (MNEs) into emerging market countries. This issue is important as globalization and the increasing amount of foreign direct investments have made emerging market countries even more important for multinational enterprises. Successful business operations in emerging market countries often rely on the management of political risks as those risks are the most crucial risks to be taken into account in emerging markets. This thesis will cover all the main types of political risks and explain what political risks essentially are. The thesis divides political risks into two main categories: non-violent political risks and violent political risks. These two groups explain the most common ways that political risks appear. Additionally, this thesis will discuss political risk management in the emerging markets. There are three different perspectives on political risk management and those will be explained thoroughly. The perspectives are the institutional view, the resources and capabilities view, and the resource dependence view. All of these perspectives see political risk in different ways and treat political risk in various manners. To give MNEs some concrete ways to manage political risks, this thesis will also discuss three approaches on how political risk can be dealt with. These approaches are the reactive approach, the proactive approach, and the active approach. The thesis discovers that it is possible to manage political risks even in emerging market countries. MNEs need to be aware of possible risks and understand the environment that they operate in. The management of political risks is crucial especially in emerging markets as in those markets the management of political risk can be the factor that determines if the MNE can invest in the region. This thesis also discovers that there are multiple ways to look at political risk and that some companies see political risks as threats, and some see them as opportunities. In the future political risks need to be considered by MNEs more than before as increasingly more countries becomes emerging market countries with diverse political risks.

Tämän tutkielman tarkoituksena on tutkia, miten poliittiset riskit vaikuttavat monikansallisten yritysten kansainvälistymiseen kehittyvien markkinoiden maihin. Tämä kysymys on tärkeä, koska globalisaatio ja ulkomaisten suorien sijoitusten määrän kasvu ovat tehneet kehittyvien markkinoiden maista entistä tärkeämpiä monikansallisille yrityksille. Kehittyvien markkinoiden maissa menestyvä liiketoiminta nojaa usein poliittisten riskien hallintaan, sillä nämä riskit ovat keskeisimpiä kehittyvillä markkinoilla huomioitavia riskejä. Tämä tutkielma kattaa kaikki poliittisten riskien päätyypit ja selittää, mitä poliittiset riskit olennaisesti ovat. Tutkielma jakaa poliittiset riskit kahteen pääryhmään: ei-väkivaltaiset poliittiset riskit ja väkivaltaiset poliittiset riskit. Nämä kaksi ryhmää selittävät yleisimmät tavat, joilla poliittiset riskit ilmenevät. Lisäksi tutkielmassa käsitellään poliittista riskienhallintaa kehittyvillä markkinoilla. Poliittisesta riskienhallinnasta on kolme erilaista näkökulmaa, jotka selvitetään perusteellisesti. Näkökulmia ovat institutionaalinen näkemys, resurssi- ja kykynäkökulma sekä resurssiriippuvuusnäkökulma. Kaikki nämä näkökulmat näkevät poliittisen riskin eri tavoin ja käsittelevät poliittista riskiä eri tavoin. Jotta monikansalliset yritykset saisivat konkreettisia tapoja hallita poliittisia riskejä, tässä tutkielmassa käsitellään myös kolmea lähestymistapaa siihen, miten poliittisia riskejä voidaan hallita. Nämä lähestymistavat ovat reaktiivinen lähestymistapa, ennakoiva lähestymistapa ja aktiivinen lähestymistapa. Tutkielmassa todetaan, että poliittisia riskejä on mahdollista hallita myös kehittyvien markkinoiden maissa. Monikansallisten yritysten on oltava tietoisia mahdollisista riskeistä ja ymmärrettävä toimintaympäristöään. Poliittisten riskien hallinta on ratkaisevan tärkeää erityisesti kehittyvillä markkinoilla, sillä näillä markkinoilla poliittisten riskien hallinta voi olla tekijä, joka määrittää, voiko monikansallinen yritys investoida alueelle. Tutkielmassa todetaan myös, että on olemassa useita tapoja tarkastella poliittista riskiä, ja että jotkut yritykset näkevät poliittiset riskit uhkina, ja jotkut näkevät ne taas mahdollisuuksina. Tulevaisuudessa monikansallisten yritysten on otettava poliittiset riskit entistä paremmin huomioon, kun yhä useammista maista tulee kehittyvien markkinoiden maita, joissa on erilaisia poliittisia riskejä.
Keywords: political risk, emerging market, multinational enterprise, risk management poliittinen riski, kehittyvät markkinat, monikansallinen yritys, riskienhallinta